WAYS TO DEVELOP THE GREEN ECONOMY AND GREEN JOBS - Begimkulova Gulhayo Bakhtiyorovna (Journals Park Publishing, 2024)
This article covers in detail the economic models that use natural resources wisely and protect the environment and aim to achieve social well-being, as well as the professions that operate in the areas of the green economy and contribute to sustainable development.
Keywords: Green economy, green jobs, green zones, International Labor Organization (ILO).